HISTOPATHOLOGICAL CHANGES (GILLS AND LIVER) AND CLINICAL SIGNS OF COMMON CARP, CYPRINUS CARPIO L. EXPOSED TO GRAPHENE NANOPARTICLES - & Khalel, Al-Rudainy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was conducted to investigate the effect of graphene nanoparticles on histopathological changes and clinical signs of common carp Cyprinus carpio. A total of 48 fish were used in the experiment with an average weight 68.44 g. Fish were exposed to graphene nanoparticles at concentrations of 10 and 20 mg / L for the T1 and T2 respectively, as well as to control group (without graphene nanoparticles). Fish exposed to graphene showed no abnormal behavior and no mortality satisfactory clinical signs in the experimental fish. Histopathological changes of gills showed fusion with shorting of the secondary lamellae, lifting up secondary lamellae beside necrosis and hyperplasia of the epithelial cells of secondary lamellae in gills. On the other hand, there was necrosis of hepatocytes, dilation of sinusoids, hydrobic degeneration, hepatocellular vacuolation, hypertrophy and hydrobic of degeneration in liver. The present study was suggested to investigate of the graphene nanoparticles effects on histopathological changes and clinical signs to clarify a clear representation about on fish and its danger of its accumulation in aquatic environment.